A reforma educacional Paraguaia de 1994 - Roesler, Patricia Simone (2015)
The focus of this study is the Paraguayan educational reform of 1944 during the period from 1990 to 1998. The analysis is based on the premise that every reform occurs in response to a social need, thus, the effort focuses on gauging what issue this reform method of education sought to resolve. The conclusion recorded through document and bibliographic research highlighted that the materiality of educational precariousness of the nation was real, however, the planning, elaboration and implementation of the reform process had its development and execution compromised and restricted, mostly due to the external interference, which does not constitute as a national identity, a priori, to contemplate the expectations and needs of the nation. Therefore, it was part of a set of measures designed in accordance with the interests of the USA, which imposed on education its adequacy with the development demands of capitalist society aligned with the neoliberal globalization.